Analisis Determinan Ekspor Komoditas Utama Sumatera Barat ke Negara Mitra Dagang - Novi, Olivia Putri; Satrianto, Alpon (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of Gross Domestic Product (GDP), Distance, Inflation, Exchange Rate, and Export Prices on the export value of animal/vegetable fats and oils from West Sumatra. The method used in this research is panel data analysis covering seven partner countries over the period 2016–2022, using a Fixed Effect Model (FEM) approach. The dependent variable in this study is the export value of animal/vegetable fats and oils, while the independent variables consist of the partner countries. GDP, distance, inflation, exchange rate, and export prices. The results of the study indicate that the GDP of partner countries and export prices have a significant positive effect on the export value of animal/vegetable fats and oils from West Sumatra. In contrast, distance, inflation, and exchange rate have a significant negative effect on the export value of these commodities.